What keeps mobile in ageing? A comparison of balance, physical activity and social integration between 60- to 80-year-old healthy people who regularly dance, do sports or are active in everyday life - a cross-sectional study / Was hält im Alter mobil? Gleichgewicht, körperliche Aktivität und soziale Integration im Vergleich zwischen 60- bis 80-jährigen gesunden Personen, die regelmäßig tanzen, Sport betreiben oder im Alltag aktiv sind - eine Querschnittstudie - Kidritsch Anita; Grossauer Rafael; Sandhofer Valerie; Teichmeister Lisa; Vesely Sarah; Wachermayr Katharina (Sciendo, 2024)
Physical and social activity can influence positively the effects of ageing. This study examined differences in balance, physical activity and social integration between everyday active, sportive or dancing 60- to 80-year-old people in Lower Austria.